What Do German Short-Term Interest Rates Tell Us About Future Inflation? - Harald Grech (Oesterreichische Nationalbank (OeNB), 2004)
In this paper, the author empirically assesses the predictive power of short-term interest rates and term spreads for future inflation in Germany. Based on a multivariate term structure framework, a vector error forecasting equation for inflation forecasts of up to two years is constructed. The results of the alternative error correction reveal that the level of the shortterm interest rates conveys much more information on future inflation than the yield curve spreads. In particular, the one-month and three-month nominal interest rates seem to be informative on future inflation at a two-year horizon.
Keywords: E31; C51; 330; inflation; interest rates